PENGARUH STRUKTUR KEPEMILIKAN, PROFITABILITAS DAN AGRESIFITAS PAJAK TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TAMBANG YANG TERDAFTAR DI BEI - Diah Ayu Gustiningsih; Basri Modding; Mursalim Mursalim (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This research was conducted with the aim of: (1) examine and analyze the influence of institutional ownership structure effect on corporate social responsibility disclousure, (2) examine and analyze the influence of managerial ownership structure effect on corporate social responsibility disclousure (3) test and analyze the effect on the profitability of the corporate social responsibility disclousure, (4) test and analyze the influence of tax aggressive effect on corporate social responsibility disclousure. This research using secondary data financial stattement from 2010 until 2013 on BEI of South Sulawesi Province with population of 25 minning corporate and 12 corporate are sampled. This study uses multiple linear regression as a tool to analyze the data, and processed with statistical program SPSS 21.0. he results of this study show that, (1) institutional ownership has no effect on the corporate social responsibility disclosure.(2) influence the effect of managerial ownership on the corporate social responsibility disclosure. (3) Profitability has no effect on the corporate social responsibility disclosure (4) Tax Aggressiveness effect on corporate social responsibility disclosure.